English Grammar : (Video Aided Instruction, 2004)
Video Aided Instruction's English Grammar Series makes the tricky rules of English grammar easier to learn than ever before - whether you're new to English or you've been speaking it for years! Perfect for classroom use or self-study, this program uses easy-to-follow examples and practice exercises from everyday life to help you master even the most complicated English grammar topics! It's also great for reviewing forgotten grammar or preparing for many verbal standardized exams such as the SAT, TOEFL, GED, and GRE. Plus, it can really help you improve your grades in school or advance your career! Like most languages, English strings words together into sentences in order to communicate ideas. But many people find it difficult to construct English sentences correctly. This program will teach you the basic principles that govern how English sentences are constructed, and how to put these principles to use when you create your own sentences! So don't let mistakes in English grammar embarrass you - now you can eliminate them from your speaking and writing forever.